2009
DOI: 10.1007/s00033-009-0021-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a mode-III crack in the presence of surface elasticity and a prescribed non-uniform surface traction

Abstract: We consider an elastic solid incorporating a mode-III crack in which the crack faces incorporate the effects of surface elasticity and are further subjected to prescribed non-uniform surface tractions. The surface elasticity is modelled using the continuum-based model of Gurtin and Murdoch. Using complex variable techniques, the corresponding problem is reduced to the solution of a first order Cauchy singular integro-differential equation which, in turn, leads to the complete solution of the aforementioned cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 9 publications
1
33
3
Order By: Relevance
“…This result is in agreement with the recent papers [Kim et al 2013;Walton 2012] where it was noted that by imposing the further condition θ ≡ 0 at the crack tips (to achieve finite stress [Kim et al 2010a; 2010b]) we effectively overdetermine the problem so that, contrary to the results reported in these two references, there can be no solutions of (2.2)-(2.4) with finite stress at the crack tips. In fact, this is clear from the DISPLACEMENT FIELD IN AN ELASTIC SOLID WITH CRACK AND SURFACE EFFECTS 789 uniqueness theorem proved above: once the unique displacement field is determined in the body one cannot then arbitrarily assign values to the derivatives of the displacement field at the crack tips.…”
Section: Integral Equationsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is in agreement with the recent papers [Kim et al 2013;Walton 2012] where it was noted that by imposing the further condition θ ≡ 0 at the crack tips (to achieve finite stress [Kim et al 2010a; 2010b]) we effectively overdetermine the problem so that, contrary to the results reported in these two references, there can be no solutions of (2.2)-(2.4) with finite stress at the crack tips. In fact, this is clear from the DISPLACEMENT FIELD IN AN ELASTIC SOLID WITH CRACK AND SURFACE EFFECTS 789 uniqueness theorem proved above: once the unique displacement field is determined in the body one cannot then arbitrarily assign values to the derivatives of the displacement field at the crack tips.…”
Section: Integral Equationsupporting
confidence: 91%
“…In the case of antiplane deformations of a linearly elastic and homogeneous isotropic solid containing a sharp crack, Kim et al [2010a; have incorporated surface effects on the faces of the crack using the Gurtin-Murdoch surface elasticity model [Gurtin and Murdoch 1975;1978;Ru 2010]. The resulting mathematical model gave rise to a nonstandard boundary-value problem for the (harmonic) antiplane displacement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, various authors (see, for example, [Kim et al 2010b;2010a;2011a;2011b;2011c;Antipov and Schiavone 2011;Wang 2015]) have incorporated the continuum-based surface/interface theory of Gurtin and Murdoch [1975;1978;Gurtin et al 1998] into the fracture analysis of linearly elastic solids. It was shown that the incorporation of the Gurtin-Murdoch surface model can suppress the classical strong square-root stress/strain singularity at the crack tip predicted in linear elastic fracture mechanics (LEFM) to the weaker logarithmic singularity [Walton 2012;Kim et al 2013].…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent papers have adopted the Gurtin-Murdoch surface elasticity paradigm for modeling the constitutive behavior of the surface stress tensor [12,8,10,9,11]. However, it has been shown (first in [15] and subsequently corroborated in [7]) that while this choice of crack-surface stress tensor constitutive relation does remove the strong (square-root) cracktip stress/strain singularity, it is replaced by a weak, logarithmic one.…”
Section: Introductionmentioning
confidence: 99%